An interim note on machining super high tensile steel - Purcell, J.; Ellis, P.J.; Vicary, D.P. (College of Aeronautics, 1958)
A series of tests have been carried out to determine the machinability characteristics of Ultra High Tensile Steels in the 120 tons sq. ins. T/S range with hardness values of 550 to 600 V.P.N. Tool geometry and cutting conditions for end and face milling, drilling and tapping were investigated. A basic approach to tapping tests and tap design was developed. Short descriptions of the tests and a graphical presentation of the results are included. These show optimum conditions and the very critical nature of the variables on tool efficiency for the processes of drilling and end and face milling, under finishing conditions